2018
DOI: 10.26725/jee.2018.4.30.6173-6176
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Farm Women Groups in the Planning, Production and Marketing Aspects of Vegetables in Kerala

Abstract: Kerala is a consumer state as far as vegetables are concerned. Major share of the fresh vegetable supply for the state comes from neighbouring states. Promoting vegetable cultivation in the state coupled with suitable marketing mechanism will not only help to make the state self reliant in vegetable production but also ensure year round availability of quality vegetables. The study was conducted in six panchayats of Kollam district in Kerala which includes the selected women groups of Kudumbashree, Vegetable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Mukherjee et al, concluded that if a farmer becomes member of an organization they will have timely access to input supply and value added services which resulting in higher quality produce and a stronger market profit [4]. Chandran and Sreedaya found that an increase in income showed positive relationship with planning, production and marketing aspects of vegetables among farm women groups [5]. The main reason for this was that working in a group creates synergy among the farmers and enables them to access market information as well as sharing experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Mukherjee et al, concluded that if a farmer becomes member of an organization they will have timely access to input supply and value added services which resulting in higher quality produce and a stronger market profit [4]. Chandran and Sreedaya found that an increase in income showed positive relationship with planning, production and marketing aspects of vegetables among farm women groups [5]. The main reason for this was that working in a group creates synergy among the farmers and enables them to access market information as well as sharing experiences.…”
Section: Introductionmentioning
confidence: 99%